Survei Keterampilan Teknik Dasar Bulutangkis Fase D - Risqi Bustanul Arifin; Dona Sandy Yudasnara; Zihan Novita Sari (Journal Sport Science Indonesia, 2024)
The game of badminton has several basic techniques that need to be mastered to be able to play badminton, starting from serves, lobs and drive shots. However, based on previous literature studies, many students still have poor basic techniques for playing badminton, such as students' ability to perform basic badminton techniques often encounter errors and also many students play without direction from educators, many are embarrassed to carry out basic technical movements. badminton. The aim of this research is to determine the basic skills of playing badminton. The method used in this research is research that uses survey methods and quantitative descriptive data types. There were two questionnaires used, the first was an analysis questionnaire on the availability of evaluation tools for physical education, sports and health and the second questionnaire was a movement observation instrument for basic badminton skills. The results of this survey research show the level of basic technical skills in the game of badminton, namely that the observation results for men's serves show results that tend to be good at 84.8% and for women's serves tend to be poor at 55.5%. Furthermore, for men's lob skills, the results tend to be less, namely 60.0% and for women's lob, they tend to be less or 58.25%. For men's drive skills, it tends to be moderate, namely 66.9% and for women, it tends to be very low, namely 45.5%. So it can be concluded that in the phase D badminton skills survey research, the average student tends to have skills that are on the low side, therefore improvements need to be made.